Pediatric and young adult renal cell carcinoma. Issue 11 (1st September 2020) - Ray, Satyajit; Jones, Robert; Pritchard‐Jones, Kathy; Dzhuma, Kristina; van den Heuvel‐Eibrink, Marry; Tytgat, Godelieve; van der Beek, Justine; Oades, Grenville; Murphy, Dermot
Abstract: Renal cell carcinoma (RCC) is rare in children but is the most common renal tumor in adults. Pediatric RCC has different clinical characteristics, histopathology, and treatment compared with adult disease. Databases were reviewed from inception to February 2020, identifying 32 publications pertaining to 350 patients under 27 years. Surgery is the cornerstone for cure in localized RCC. Lymph node dissection remains controversial. Conventional radiotherapy has no curative role in RCC; similarly, conventional chemotherapy has not proven to be effective in large cohorts. Pediatric metastatic RCC has a poor outlook. There are no published prospective studies demonstrating which adjuvant therapy could improve outcome. Sunitinib, a tyrosine kinase inhibitor, is recommended in this group despite limited evidence. This review provides an overview for pediatric RCC, including the evolving role of precision medicine.